Differences in the regional stratigraphy of NE Poland caused by vertical movements due to glacioisostasy - Morawski, Wojciech (Geologos, 2009)
Geological mapping in combination with geophysical investigations and borehole analyses show differences of the Pleistocene between the Warmia and Mazury palaeogeographic provinces in NE Poland. The (more western) Warmia province has a crystalline basement that is covered by a folded sedimentary succession of 2–4 km thick. The (more eastern) Mazury province (eastern) has a basement that forms part of the rigid East European crystalline craton, which is covered by a sedimentary cover of only 1–1.5 km thick. Cyclic loading by the Pleistocene ice sheets in this area induced glacioisostatic processes of different intensities, resulting in changing palaeogeographic conditions. The changes were increased by intense neotectonic activity that was induced by the ice sheets in the intermediate zone between the two provinces, stretching along the western slope of the crystalline craton. Significant part of intermediate zone forms a belt of crevasse-infill landforms deposited between the Warmia and Mazury lobes of the last glaciation. Studied deposits reveal a cyclic reactivation of the interlobe zone during the successive Pleistocene glaciations. Considerable variations of the relief of the top-Neogene, vertical discontinuities cutting the Pleistocene and Neogene, stratigraphic gaps within the Pleistocene succession, and thick glaciolacustrine successions result from the vertical neotectonic movements in the intermediate area between the two provinces.